Identifying Poly-Victimization Among Prisoners: An Application of Latent Class Analysis - Azimi, Andia M. (Journal of interpersonal violence, 2021)
Research suggests that people in prison may be especially vulnerable to victimization and may be more likely to report exposure to multiple types, known as poly-victimization. However, the literature surrounding patterns of victimization among prisoners is limited. Before we can fully understand the variation in victimization experiences among prisoners, a necessary first step is to identify victim profiles within prisons. The current study utilizes data from the 2004 Survey of Inmates in State and Federal Correctional Facilities and employs latent class analysis to identify unique victim profiles among prisoners to understand the variation in victimization experiences, with a focus on identifying those exposed to poly-victimization. The findings of this study indicate (a) that there are four distinct victim profiles—poly-victimization (2%), physical victimization in adulthood (31%), physical victimization in childhood (17%), and low/no victimization (49%); (b) that some prisoners experience poly-victimization, although this consists of a small proportion of prisoners; and (c) that there are clear demographic differences between the latent classes, with some of the largest differences among those in the poly-victimization profile. The findings of the current study are important because they add more depth to the knowledge regarding poly-victimization among prisoners, a topic that has received little attention from researchers. The current study suggests that correctional policy may need to be tailored in a way that recognizes the different needs of prisoners who have been exposed to different forms of victimization.